Providing of Spatial Wetland Information for Supporting National Development - Poniman, Aris; Nurwadjedi, Nurwadjedi; Suwahyuono, Suwahyuono (Forum Geografi, 2006)
The wetland has a strategic role in national development. The potential uses of the wetland are varied such as for agriculture, fisheries, industries, and forestry. The intensive use of the wetland for agricultural development in Sumatera, Kalimantan, Sulawesi, and Papua through transmigration projects has been run since in 1973. Unfortunately, not all the projects were well developed, causing the social, economic, and physical environmental problems. These problems resulted in the negative impact for the life of the transmigration people. For that reason, the community empowerment for the unlucky transmigration people by handling the physical and non physical aspects is very important. This paper will describe the importance of providing spatial data and information biophysical wetland as an initial step in empowering people who live in the wetland resource.